Later school start times for supporting the education, health, and well‐being of high school students. Issue 1 (19th December 2017) - Marx, Robert; Tanner‐Smith, Emily E; Davison, Colleen M; Ufholz, Lee‐Anne; Freeman, John; Shankar, Ravi; Newton, Lisa; Brown, Robert S; Parpia, Alyssa S; Cozma, Ioana; Hendrikx, Shawn
Abstract : This Campbell systematic review examines the impact of later school start times on student academic performance, mental health and family and community outcomes. The review summarises findings from 17 reports of 11 interventions in six countries. Later school start times appear to increase sleeping time. And there is a positive association between later school start times and academic and psychosocial outcomes. The evidence on absenteeism and student alertness is mixed. However, the quality of the evidence and comparability of studies is low. Adverse effects may be reduced interaction with parents, and staffing and scheduling difficulties. There is insufficient evidence to draw firm conclusions concerning these possible adverse effects. Executive summary/Abstract: Background: A number of school systems worldwide have proposed and implemented later school start times as a means of avoiding the potentially negative impacts that early morning schedules can have on adolescent students. Even mild sleep deprivation has been associated with significant health and educational concerns: increased risk for accidents and injuries, impaired learning, aggression, memory loss, poor self‐esteem, and changes in metabolism. Although researchers have begun to explore the effects of delayed school start time, no one has conducted a rigorous review of evidence to determine whether later school start times support adolescent health, education, and well‐being. Objectives: We aimed to assess the effects of a later school start time for supporting health, education, and well‐being in high school students. Secondary objectives were to explore possible differential effects of later school start times in student subgroups and in different types of schools; to identify implementation practices, contextual factors, and delivery modes associated with positive and negative effects of later start times; and to assess the effects of later school start times on the broader community (high school faculty and staff, neighborhood, and families). Search methods: We conducted the main search for this review on 28 October 2014 and updated it on 8 February 2016. We searched CENTRAL as well as 17 key electronic databases (including MEDLINE, Embase, ERIC, PsycINFO, and Sociological Abstracts), current editions of relevant journals and organizational websites, trial registries, and Google Scholar. Selection criteria: We included any randomized controlled trials, controlled before‐and‐after studies, and interrupted time series studies with sufficient data points that pertained to students aged 13 to 19 years and that compared different school start times. Studies that reported either primary outcomes of interest (academic outcomes, amount or quality of sleep, mental health indicators, attendance, or alertness) or secondary outcomes (health behaviors, health and safety indicators, social outcomes, family outcomes, school outcomes, or community outcomes) were eligible. Data collection and analysis: At least two review authors independently determined inclusion and exclusion decisions through screening titles, abstracts, and full‐text reports. Two review authors independently extracted data for all eligible studies. We presented findings through a narrative synthesis across all studies. When two or more study samples provided sufficient information to permit effect size calculations, we conducted random‐effects meta‐analyses to synthesize effects across studies. Results: Our search located 17 eligible records reporting on 11 unique studies with 297, 994 participants; the studies examined academic outcomes, amount and quality of sleep, mental health indicators, attendance, and student alertness. Overall, the quality of the body of evidence was very low, as we rated most studies as being at high or unclear risk of bias with respect to allocation, attrition, absence of randomization, and the collection of baseline data. Therefore, we cannot be confident about the effects of later school start times. Preliminary evidence from the included studies indicated a potential association between later school start times and academic and psychosocial outcomes, but quality and comparability of these data were low and often precluded quantitative synthesis. Four studies examined the association between later school start times and academic outcomes, reporting mixed results. Six studies examined effects on total amount of sleep and reported significant, positive relationships between later school start times and amount of sleep. One study provided information concerning mental health outcomes, reporting an association between decreased depressive symptoms and later school start times. There were mixed results for the association between later school start times and absenteeism. Three studies reported mixed results concerning the association between later school start times and student alertness. There was limited indication of potential adverse effects on logistics, as the qualitative portions of one study reported less interaction between parents and children, and another reported staffing and scheduling difficulties. Because of the insufficient evidence, we cannot draw firm conclusions concerning adverse effects at this time. It is important to note the limitations of this evidence, especially as randomized controlled trials and high‐quality primary studies are difficult to conduct; school systems are often unwilling or unable to allow researchers the necessary control over scheduling and data collection. Moreover, this evidence does not speak to the process of implementing later school starts, as the included studies focused on reporting the effects rather than exploring the process. Authors' conclusions: This systematic review on later school start times suggests several potential benefits for this intervention and points to the need for higher quality primary studies. However, as a result of the limited evidence base, we could not determine the effects of later school start times with any confidence.